SINTESIS 3-(4-BROMOFENIL)-1-(NAFTALEN-1-IL)PROP-2-EN-1-ON DARI 1-ASETILNAFTALEN DENGAN 4-BROMOBENZALDEHID - R. I. P. Sari; Yuharmen '; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Chalcone of 3-(4-Bromo-phenyl)-1-naphthalen-1-yl-propenone was synthesizedby the stirring method in Claisen-Schmidt Condensation with NaOH as the catalyst. Thestructure of the compound was confirmed by 1 H-NMR, 13 C-NMR, IR, MS, and UVspectroscopy method. The compound produced was in 81.9% yields. Datacharacterization showed that the compound obtained was the targetted compound.